2013
DOI: 10.1097/cad.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies to minimize toxicity of oxaliplatin

Abstract: Oxaliplatin is an anticancer drug routinely used to treat colorectal, gastroesophageal, ovarian, breast, head/neck, and genitourinary cancers. Discontinuation of oxaliplatin treatment is mostly because of peripheral neuropathy, more often than for tumor progression, potentially compromising patient benefit. Several strategies to prevent neurotoxicity have so far been investigated. To overcome this life-threatening side effect, while taking advantage of the antineoplastic activities of oxaliplatin, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…4 Nevertheless, the low selectivity of platinum( ii ) drugs towards cancer cells and cancerous tissue, together with severe adverse effects are still major disadvantages. 5,6 An approach to enhance the selectivity are platinum( iv ) prodrugs, which are chemically more inert and thus less cytotoxic. After entering the hypoxic, reductive conditions of the cancerous tissue, they are reduced and release their active, highly cytotoxic Pt( ii )-core (activation by reduction).…”
Section: Introductionmentioning
confidence: 99%
“…4 Nevertheless, the low selectivity of platinum( ii ) drugs towards cancer cells and cancerous tissue, together with severe adverse effects are still major disadvantages. 5,6 An approach to enhance the selectivity are platinum( iv ) prodrugs, which are chemically more inert and thus less cytotoxic. After entering the hypoxic, reductive conditions of the cancerous tissue, they are reduced and release their active, highly cytotoxic Pt( ii )-core (activation by reduction).…”
Section: Introductionmentioning
confidence: 99%
“…Our results compared favorably with pCR rates of 8%-15% among historical controls treated with fluoropyrimidine-based CRT in patients with locally advanced rectal cancer [6,[18][19][20][21][22][23][24][25][26][27][28]. Based on its role in resected stage III colon cancer and its radiosensitizing properties, the addition of oxaliplatin to the standard fluoropyrimidine-based CRT was tested in many studies [1].…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration reported that more than 70% of patients receiving oxaliplatin had some degree of peripheral neuropathy [20], which is often the cause for treatment discontinuation. Despite these adverse life-altering side effects, oxaliplatin therapy is a treatment choice in a large group of cancer patients, including those with colorectal cancer [21]. In this study, this approach (preoperative fluorouracil, leucovorin, and oxaliplatin withnoradiotherapy [RT])inpatients with locally advanced rectal cancer was tested in a prospective pilot study.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of DNA repair elements to treat CIPN is an emerging field. Ongoing studies are investigating diagnostic markers, molecular mechanisms, drug comparisons and potential treatments for CIPN [116–118]. Development of an effective small-molecule DNA repair inhibitor would be a first-in-class drug for neuropathic pain, which could change both survival and quality-of-life outcomes for many cancer patients.…”
Section: Dna Inhibition As Treatment For Chemotherapy-induced Periphementioning
confidence: 99%